(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of nonsuicidal self-injury, depression, anxiety, and stress and examine their associations among students at Tan Phu High School, Dong Nai province in 2025. Subjects and methods: A cross-sectional study was conducted among 996 students at Tan Phu High School from September 2024 to April 2025. Data were collected using a self-administered questionnaire including demographic information, the DASS-21, and the FASM. Results: The prevalence of nonsuicidal self-injury was 34.4%. The prevalence of depression, anxiety, and stress was 50.2%, 59.5%, and 50.8%, respectively. Students with depression, anxiety, and stress were 1.66, 1.69, and 1.53 times more likely to engage in nonsuicidal self-injury compared with those without these conditions. Conclusions: Nonsuicidal self-injury among students at Tan Phu High School was relatively common and was significantly associated with depression, anxiety, and stress. Early detection and psychological support interventions in schools are needed.